Effect of endoscopic augmentation of the lower oesophageal sphincter (Gatekeeper reflux repair system) on intraoesophageal dynamic characteristics of acid reflux. Issue 2 (11th January 2005) - Cicala, M; Gabbrielli, A; Emerenziani, S; Guarino, M P L; Ribolsi, M; Caviglia, R; Costamagna, G
Abstract : Background and aims: Improvements in symptoms following endoscopic procedures for gastro-oesophageal reflux disease (GORD) are seldom supported by normalisation of acid exposure time at the distal oesophagus. However, the distribution of gastric acid within the proximal oesophagus is a main determinant of symptom generation in GORD patients. In this study, our aim was to assess the effect of endoscopic insertion of hydrogel expandable prostheses into the oesophageal submucosa on spatiotemporal characteristics of gastro-oesophageal reflux. Methods: Oesophageal manometry and multichannel ambulatory 24 hour pH monitoring were carried out in nine patients before and six months after the endoscopic procedure. Dynamic characteristics of gastro-oesophageal reflux in patients were also compared with those in 13 asymptomatic controls. Results: Acid exposure time (AET) at the distal oesophagus decreased from 11.7% (95% confidence interval 6.1–21.8) at baseline to 7.7% (3.7–11.6) at follow up (NS). Of the nine patients, distal AET normalised in three. AET at the middle (7.6% (2.9–12.3)) and proximal (2.4% (0.1–4.8)) oesophagus decreased significantly in all patients (2.4% (0.3–4.5), p <0.01; 1.2% (0.2–2.2), p<0.05 respectively). Proximal extent of acid events significantly decreased in all patients at follow up (37.3% v 9.5%), reaching values observed in asymptomatic controls. Median GORD health related quality of life scores significantly improved from 35.5 at baseline to 9.4. Conclusions: Despite the lack of a significant improvement in traditional pH variables, endoscopic implant of hydrogel prostheses above the lower oesophageal sphincter significantly decreases proximal spread of acid reflux into oesophageal body. This effect would explain the improvement in symptoms in patients six months after therapy.